PENGEMBANGAN DAERAH WISATA PADA DESA BUDAYA KERTALANGU DESA ADAT KESIMAN KOTA DENPASAR - Rahayu, Ni Putu Indah; Dewi, Nyoman Diah Utari; Widnyani, Ida Ayu Putu Sri (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2024)
Regional tourism development is a government program that increases regional income. The tourism industry has an important role in the economic growth of the people. Kertalangu Cultural Village is a tourist spot that prioritizes environmental and cultural preservation This village was inaugurated in 2007 and designated as a cultural village based on the Decree of the Mayor of Denpasar No. 25 of 2008. This study aims to determine the obstacles that occur in the development of Kertalangu Village as a cultural village and the impacts arising from the existence of Kertalangu Cultural Village. This study uses qualitative methods with data collection through literature studies and documentation. The results of this study are first, related to obstacles in the development of Kertalangu Cultural Village there are two obstacles, namely less than optimal management management, this can be seen from the lack of promotion of existing activities and facilities, besides that it is necessary to maintain the environment to keep it clean. Another obstacle is the limited budget, this is due to the small income from cultural villages, which requires expensive maintenance costs. Second, related to the impact of the development of Kertalangu Cultural Village, there are three impacts: (1) economic impact, namely the impact on the surrounding community whose land is leased for development, that it also reduces unemployment of the surrounding community, (2) socio-cultural impact, the development of Kertalangu Cultural Village does not have an impact on the social life of the surrounding community, but has an impact on community culture because Kertalangu Cultural Village holds events certain and carry out art performances, (3) environmental impacts, the development of Kertalangu Cultural Village does not have a negative impact on preserving the surrounding environment, even the community holds a reforestation program in Kertalangu Cultural Village. Keywords: Constraints; Impacts; Cultural Villages